AN ANALYSIS OF PERCEIVED CREDIBILITY AND SHARIA COMPLIANCE IN DIGITAL FINANCIAL APPLICATIONS - Muhamad Farid Al Fathdry; Ries Wulandari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The digital transformation in the financial sector presents complex challenges regarding platform credibility and sharia compliance, particularly for service providers operating in a two-sided market ecosystem. This study aims to deconstruct provider perceptions regarding application credibility defined through cost transparency and security as well as sharia compliance, and how these factors influence adoption and retention decisions. Using the Analytic Network Process (ANP) method, this research synthesizes assessments from five experts (academics and practitioners) to map problem and solution priorities within the Indonesian Islamic digital finance ecosystem. The findings indicate that internal problems, specifically system security aspects (weight 0.466), are the primary priority, preceding cost transparency and sharia compliance. Conversely, the most effective solutions are external, where the publication of verified track records through independent audits and certifications (weight 0.652) is considered the most critical determinant for user retention sustainability. These results imply that a sharia label alone is insufficient; platform providers must invest in external validation mechanisms to overcome information asymmetry and build long-term trust.